Organic carbon stock and physical soil attributes in a crop-forest and eucalyptus integration system in the Cerrado Mineiro (Research, Society and Development, 2022)
The crop-forest integration system (ILF) integrates the forestry and agricultural component. This study aimed to evaluate organic carbon stocks and soil physical attributes under a crop-forest integration system, in southwestern Minas Gerais. The study was carried out at the Experimental Farm of the Universidade do Estado de Minas Gerais, Academic Unit of Passos. The experimental design used was in randomized blocks, with three treatments and seven replications. The effect of this system on soil attributes was tested by means of analysis of variance. The effects of treatments were evaluated considering the position of row and between rows. When there was a significant effect (P